Quantitative determination of antibody to capsular polysaccharide in infection with type III strains of group B Streptococcus. - Baker, C J (1977)
The development of antibody in response to invasive infection with type III strains of group B Streptococcus was studied in sera from 31 infants and 4 adults by means of a quantitative radioactive antigen-binding assay. Low concentrations of antibody were consistently found in the acute sera of patients who developed clinical illness. Although adults with puerperal sepsis and infants with bone or joint infection uniformly demonstrated significant rises in serum antibody concentration after recovery, much lower levels of antibody were detected in convalescent sera from infants recovering from meningitis or sepsis. The median antibody concentration in sera from 43 parturients with type III strains of group B Streptococcus isolated from vaginal cultures whose neonates failed to develop symptomatic disease was significantly greater than that in sera from 29 mothers of infants with invasive, type III, group B streptococcal infection. Study of paired maternal and cord sera demonstrated a significant correlation between the antibody concentration in a mother's serum and that in her neonate.